2016
DOI: 10.1523/jneurosci.1743-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the GluN2A/GluN2B Ratio in Neurons of the Mouse Basal and Lateral Amygdala Inhibits the Modification of an Existing Fear Memory Trace

Abstract: Reconsolidation updating is a form of memory modification in which an existing memory can become destabilized upon retrieval and subsequently be modified via protein-synthesis-dependent reconsolidation. However, not all memories appear to destabilize upon retrieval and thus are not modifiable via reconsolidation updating approaches and the neurobiological basis for this remains poorly understood. Here, we report that auditory fear memories created with 10 tone-shock pairings are resistant to retrieval-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 65 publications
4
58
1
Order By: Relevance
“…Also, memories created with the 10 pairings training are much more robust and display impaired extinction learning, a hallmark of posttraumatic stress disorder 33 . When looking at GluN2B expression, we confirmed previous reports showing that strongly-trained animals display lower GluN2B levels than mildly trained ones 11,16 . However, here we included a home cage control group in our analysis which revealed that GluN2B is not actually downregulated by strong training.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Also, memories created with the 10 pairings training are much more robust and display impaired extinction learning, a hallmark of posttraumatic stress disorder 33 . When looking at GluN2B expression, we confirmed previous reports showing that strongly-trained animals display lower GluN2B levels than mildly trained ones 11,16 . However, here we included a home cage control group in our analysis which revealed that GluN2B is not actually downregulated by strong training.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies revealed that unlike mild fear memories, very strong ones do not destabilize upon recall 11,16 . Some of the mechanisms required to induce destabilization have been identified 1,31 , but not much is known regarding how severe fear experiences end up forming reconsolidationresistant memories.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…At the cell surface, there is a functional involvement of cholinergic [108] and dopaminergic receptors [109], at least for non-fear memory destabilization. Of particular relevance to fear memories are the necessity for cannabinoid CB1 receptor and calcium channel activity in the dorsal hippocampus [110] and NMDA receptor activity (specifically NR2B-containing NMDA receptors) in the basolateral amygdala [111114]. We and others have exploited some of these mechanisms to stimulate fear memory destabilization, in order to render effective post-reactivation treatment even under conditions that do not normally trigger reconsolidation [115117].…”
Section: The Reliability Of Reconsolidation Effectsmentioning
confidence: 99%
“…Typically, strong or remote memories have been shown to be difficult to disrupt via reconsolidation blockade. This appears to be due to the resistance of these memories to undergo retrieval-dependent memory destabilization (13)(14)(15)(16). Therefore, targeting the reconsolidation process will likely never be an effective treatment to attenuate pathological memories unless methods are devised to enhance the induction of their reconsolidation.…”
Section: Introductionmentioning
confidence: 99%